Pharyngo-occipital artery variant arising from the internal carotid artery impacting surgical technique during carotid endarterectomy. (22nd March 2012) - Graham, Randall B; Sugrue, Patrick A; Rahme, Rudy J; Batjer, H Hunt; Bendok, Bernard R
Abstract : Background and importance: Extracranial carotid artery atherosclerotic stenosis typically occurs at the junction of the common carotid, external carotid and internal carotid arteries. Although rare, anatomical arterial variants can influence surgical strategy and can have a significant impact on surgical complications and patient outcome. An unusual case of atherosclerotic stenosis of the internal carotid artery (ICA) at the origin of a pharyngo-occipital variant off of the ICA is reported here. Clinical presentation: A 60-year-old man presented with symptomatic severe left cervical ICA stenosis. The stenosis was related to the origin of the pharyngo-occipital common trunk which arose from the ICA rather than the typical origin off of the external carotid artery. The patient underwent successful left carotid endarterectomy with special attention to this variant anatomy. Conclusion: Anomalies of the extracranial ICA, although rare, can influence the location of atherosclerotic disease and the surgical endarterectomy strategy. A detailed anatomical study should be performed prior to surgery to minimize risk and improve patient outcome.